Aplikasi Nano Kompos, Nano Parti Aplikasi Nano Kompos, Nano Partikel ZnO dan SiO2 pada Pertumbuhan Bibit (Main Nursery) Tanaman Sawit: Aplikasi Nano Kompos, Nano Partikel ZnO dan SiO2 pada Pertumbuhan Bibit (Main Nursery) Tanaman Sawit - Pratiwi, Annisa Azzarah Eki Citra; Nurhidayati, Nurhidayati; Sholihah, Anis (Folium : Jurnal Ilmu Pertanian, 2025)
The main nursery is a crucial stage in oil palm seedling production before planting in the field. This study aims to explain the effect of nanocompost and nanoparticles on oil palm growth in the early stages of oil palm (Elaeis guineensis Jacq.) seedlings during the main nursery phase. The study was conducted using a simple Randomized Block Design (RAK) with various treatments P0 (Control), P1 (100% NPK (2.5 g/pot)), P2 (Nanocompost 1,000 ppm + 50% NPK), P3 (Nanocompost 500 ppm + ZnO 100 ppm + SiO2 50 ppm + 50% NPK), P4 (Nanocompost 1,000 ppm + ZnO 200 ppm + SiO2 100 ppm + 50% NPK), P5 (Nanocompost 1,500 ppm + ZnO 300 ppm + SiO2 150 ppm + 50% NPK). The results showed that the treatments P3, P4, and P5 had a significant effect on seedling growth, especially on the parameters of plant height, number of leaf sheaths, leaf area and stem diameter. Improved seedling growth is due to increased nutrient absorption efficiency and improved physical properties of the growing medium due to the application of nanomaterials. This research demonstrates that the combination of nanocompost and nanoparticles can be an innovative alternative for improving the quality of oil palm seedlings.